The relationship between depression and physical symptom burden in advanced cancer. Issue 4 (6th August 2013) - Fitzgerald, Peter; Lo, Chris; Li, Madeline; Gagliese, Lucia; Zimmermann, Camilla; Rodin, Gary
Abstract : Background: Although an association between depression and physical burden has been demonstrated in advanced cancer, it remains unclear to what extent this is limited to specific physical symptoms, such as pain and fatigue, and is mediated by disease and treatment-related factors. We therefore investigated the relationship between depression and physical burden across a multitude of physical symptoms in this population, while controlling for cancer-related factors including disease severity and proximity to death. Patients and methods: A secondary analysis was performed on cross-sectional data in 487 patients with advanced cancer. Measures included the Beck Depression Inventory II and the Memorial Symptom Assessment Scale, which measured physical burden across 24 common cancer symptoms. Disease severity was assessed by survival time and by functional status using the Karnofsky Performance Status scale. Results: Depression severity significantly correlated with number of physical symptoms, symptom distress and symptom severity independent of cancer type, functional status, chemotherapy status and survival time (all p<0.001). Depression was associated with increased incidence, severity and distress across multiple physical symptoms and was an independent predictor of physical burden on multiple regression analysis. Conclusions: These findings support the view that a synergistic relationship exists between depression and a broad array of physical symptoms in patients with advanced cancer.